Fanatisme Pemain Gim Mobile Legends pada Komunitas Kasino Squad - Shandi, Kevin January; Hidayanto, Syahrul (Jurnal Pustaka Komunikasi, 2024)
Mobile Legends is the most popular game in Indonesia currently. Its popularity then gave birth to many communities of online game lovers, one of which is the Casino Squad community. Researchers assume that several members of the Casino Squad have been identified as having fanaticism such as flaming, excessive enthusiasm, and a sense of emotional attachment and love that lasts for a long time. They show this fanaticism when playing the game Mobile Legends. This research aims to determine the forms of fanaticism in the online game players Mobile Legends and to find out the factors that cause fanaticism in the online game players Mobile Legends. This research uses a descriptive qualitative method by selecting members of the Casino Squad community as informants who are considered to have fanaticism. The research results show that online game players among members of the Casino Squad community have forms of fanaticism such as excessive playing time, excessive top ups for gacha skins and skipping school to play the Mobile Legends game. Then, the factors that cause members of the Casino Squad community to become fanatics of Mobile Legends include the game being easy to play, earning money and self-actualization